Assessing the Relative Importance of Access and Affordability in Energy Poverty in India: A Guide for Future Energy Policies - Sadath, Anver C.; Acharya, Rajesh H. (International Journal of Energy Economics and Policy, 2025)
We analyse the role of access and affordability in measuring energy poverty from a developing country context, particularly India. For this purpose, we use the Harvard Dataverse energy access database household-level data. We measure energy poverty based on subjective indicators such as the Multidimensional Energy Poverty Index (MEPI) and objective measures such as expenditure-based approaches. Empirical results show that India made substantial progress in reducing energy poverty based on all approaches, but we observe vast differences in the extent of energy poverty across different approaches. There is substantial variation in energy poverty among different socioeconomic groups and employment categories, reflecting the reality in the Indian context. Finally, we argue that access, affordability and socioeconomic variables are important determinants of energy poverty in the Indian context. Policymakers should consider these factors while designing policies to handle the problem effectively.